Disulfide bridge cross-linking between protein and the RNA backbone as a tool to study RNase H1. Issue 23 (1st December 2020) - Hyjek-Składanowska, Malwina; Stasińska, Anna R.; Napiórkowska-Gromadzka, Agnieszka; Bartłomiejczak, Aneta; Seth, Punit P.; Chmielewski, Marcin K.; Nowotny, Marcin
Graphical abstract: Abstract: The chemical cross-linking of complexes of proteins with nucleic acids is often used in structural and mechanistic studies of these oftentimes unstable and transient complexes. To date, no method has been reported for the thiol-based conjugation of proteins with an RNA backbone, mainly because of instability of the modified ribonucleic acid that is functionalized at the phosphodiester and its rapid hydrolysis. Here, we report the site-specific synthesis of stable RNA oligonucleotides with a thiol-bearing linker that was attached to the phosphodiester backbone, where the ribonucleotide at the cross-linking site was either replaced with 2′-deoxy- or 2′-fluororibonucleotide. The utility of this approach was validated in cross-linking tests with RNase H1, a model protein for RNA/DNA binding and key effector in DNA-like antisense drug therapy. Furthermore, scale-up cross-linking and purification of the complexes confirmed that the method is useful for obtaining preparations of protein-RNA/DNA complexes with purity and stability that are suitable for further biochemical and structural studies. The present approach broadens the repertoire of disulfide-based cross-linking strategies and is a novel tool for the stabilization of protein-RNA complexes in which the interaction occurs via the RNA backbone. This methodology may be broadly applicable to studies of otherwise unstable or transient complexes of proteins with RNA and RNA/DNA.